A Quasi-Steady-State Approximation to the Basic Target-Cell-Limited Viral Dynamics Model with a Non-Cytopathic Effect - Cangelosi, Richard A.; Schwartz, Elissa J.; Wollkind, David J. (Frontiers in Microbiology, 2018)
Analysis of previously published target-cell limited viral dynamic models for pathogens such as HIV, hepatitis, and influenza generally rely on standard techniques from dynamical systems theory or numerical simulation. We use a quasi-steady-state approximation to derive an analytic solution for the model with a noncytopathic effect, that is, when the death rates of uninfected and infected cells are equal. The analytic solution provides time evolution values of all three compartments of uninfected cells, infected cells, and virus. Results are compared with numerical simulation using clinical data sets for the equine infectious anemia virus, a retrovirus closely related to HIV, and the utility of the analytic solution is discussed.